Pendidikan dalam Al-Qur’an Perspektif Abdurrahman Saleh Abdullah dalam Tinjauan Filsafat Pendidikan Islam - Sholikah Sholikah; Fatah Syukur; Mahfud Junaedi; Muhammad Aziz (LPPM Institut Agama Islam Al-Hikmah Tuban, 2020)
Abstract, the thought of progressive education Abdurrahman Saleh Abdullah is inseparable from his academic turmoil because there has not been any work specifically devoted to education based on the Qur'an. Ontology education according to him is based on the existence of humans as caliphs on earth, so humans need education that has goals in accordance with the Qur'an which is seeking the pleasure of Allah. The educational objectives will not be achieved without the support of educational materials and methods. His educational thoughts cannot necessarily be applied to all societies in the world, because every community group in the world is different from the greaographic location and social conditions. Keyword, Abdurrahman Saleh Abdullah, Islamic education, Qur'anic interpretation, and Islamic Education Philosophy.